Perioperative Antibiotic Prophylaxis: Knowledge and Attitudes among Resident Physicians in Italy - Pelullo, Concetta Paola (Antibiotics (Basel), 2020)
The aim of this study is to evaluate knowledge and attitudes on the perioperative antibiotic prophylaxis (PAP) among surgery and anesthesiology resident physicians in Italy. A Web-based national survey of Italian surgery and anesthesiology resident physicians was conducted between March 2018 and January 2019. Participants completed a questionnaire and three case vignettes for each specialty. Of the 1282 resident physicians selected, 466 completed the online questionnaire for a response rate of 36.3%. More than half of the sample were female (52.9%), and the mean age was 30 years. A total of 36.3% of the participants had an adequate knowledge score about PAP. Multiple logistic regression analysis showed that resident physicians in general surgery compared to those in anesthesiology, those who agreed that PAP must be performed within 60 min before surgical incision, and those who were aware regarding the availability about the availability of national guidelines on PAP, were significantly more likely to have adequate knowledge about PAP. Moreover, 14% of participants were very concerned that patients may contract surgical site infections during hospitalization. These findings should be useful to promote educational intervention specifically targeted for surgery and anesthesiology resident physicians organizing training course on PAP, to improve the correct antibiotic use and to prevent healthcare-associated infections.